Slow wave sleep in humans: role of 5-HT2A and 5-HT2C receptors. - Sharpley, A; Elliott, J; Attenburrow, M; Cowen, P (1994)
We studied the effects of the 5-HT2 receptor antagonists, ritanserin and ketanserin, on the sleep of healthy volunteers in order to clarify the role of 5-HT2A and 5-HT2C receptors in the regulation of slow wave sleep (SWS) in humans. Ritanserin, 5 mg, produced a substantially larger increase in SWS (51.4%) than either ketanserin, 20 mg (17.2%) or ketanserin, 40 mg (24.4%). Ritanserin has a significantly higher affinity than ketanserin for 5-HT2C receptor binding sites in the human brain and, based on estimates of per cent occupancy by the two compounds at brain 5-HT2A and 5-HT2C receptors, we conclude that SWS in humans is primarily regulated by 5-HT2C receptors.